PENERAPAN DETEKSI DINI PLEBITIS ANAK YANG DIRAWAT MENGGUNAKAN SKALA INFUSION NURSE SOCIETY - Agustin, Diah Ayu (Indonesian Journal of Nursing Health Science, 2017)
AbstractMost of the hospitalized children get infusion treatment. Plebitis is one of the complications of infusion. The purpose of the study provides an overview of the application of infusion scale Nursing Society (INS) as a means of early detection of plebitis. The research method using descriptive design, with the number of samples of 35 children who installed the infusion. The data collection tool uses an observation sheet based on the scale of the INS. The data analysis used is univariate analysis. The results of the study were the majority of children treated with male sex (63%), aged less than five years (74%), there was a perception equation between the main researcher and the room nurse when determining plebitis score (100%), plebitis score score 0 there are 24 children (68%), score 1 there are 10 children (29%), score 2 there is 1 child (3%), score 3 none (0%), and score 4 none (0%). The scale conclusions of INS scale are effective, easy and feasible to use for early detection of plebitis.Â Keywords: infusion, plebitis, early detectionÂ AbstrakSebagian besar anak yang dirawat di rumah sakit mendapat tindakan pemasangan infus. Plebitis merupakan salah satu komplikasi pemasangan infus. Tujuan penelitian memberikan gambaran penerapan skala Infus Nursing Society (INS) sebagai alat deteksi dini plebitis. Metode penelitian menggunakan desain deskriptif, dengan jumlah sample 35 anak yang terpasang infus. Alat pengumpulan data menggunakan lembar observasi berdasarkan skala INS. Analisis data yang digunakan adalah analisis univariat. Hasil penelitian antara lain mayoritas anak yang dirawat berjenis kelamin laki-laki (63%), berusia kurang dari lima tahun (74%), terdapat persamaan persepsi antara peneliti utama dengan perawat ruangan saat menentukan skor plebitis (100%), distribusi skor plebitis skor 0 ada 24 anak (68%), skor 1 ada 10 anak (29%), skor 2 ada 1 anak (3%), skor 3 tidak ada (0%), dan skor 4 tidak ada (0%).Simpulan skala INS skala yang efektif, mudah dan layak digunakan untuk mendeteksi dini plebitis.Â Kata kunci: infus, plebitis, deteksi dini